2014
DOI: 10.1016/j.biomaterials.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of adipose-derived stromal cells in age-related osteoporosis

Abstract: a b s t r a c tAdipose-derived stromal cells (ASCs) are increasingly being used for orthopedic-based tissue engineering approaches due to their ability to readily undergo osteogenic differentiation. In the present study, we used in vitro and in vivo approaches to evaluate the use of ASCs as a treatment strategy for age-related osteoporosis. Molecular, histological and micro-computed tomography (micro-CT) based approaches confirmed that ASCs isolated from 18-week-old osteoporotic senescence-accelerated mice (SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 40 publications
4
47
0
4
Order By: Relevance
“…By injecting autologous BMSCs or adipose derived stem cells into local sites of osteoporotic models, bone mass and bone density at the injected site has been shown to be enhanced. 5,6,41,42 Our study demonstrated the potential of allogeneic fetal BMSCs in bone regeneration. Future studies should investigate the potential of local injection of these cells in the treatment of osteoporosis.…”
Section: Stem Cells Play An Essential Role In Tissue Regeneration Rementioning
confidence: 55%
“…By injecting autologous BMSCs or adipose derived stem cells into local sites of osteoporotic models, bone mass and bone density at the injected site has been shown to be enhanced. 5,6,41,42 Our study demonstrated the potential of allogeneic fetal BMSCs in bone regeneration. Future studies should investigate the potential of local injection of these cells in the treatment of osteoporosis.…”
Section: Stem Cells Play An Essential Role In Tissue Regeneration Rementioning
confidence: 55%
“…For application in cell therapy for osteoporosis, AD-MSCs were reported to function as an effective autologous cell-based approach for the treatment of osteoporosis. SAMP6 osteoporosis mice showed significant improvement in several trabecular bone parameters after a single intratibial transplantation of isogenic AD-MSCs [136]. A preclinical study of the in vivo function of human AD-MSCs by Cho et al revealed that human AD-MSCs could prevent OVX-induced bone loss in nude mice over 8 weeks, even though there was no evidence of long-term engraftment of infused human AD-MSCs in the bone of recipient mice [137].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, adipose-derived stem cells (ASCs) have been studied extensively as an alternative cell source to BMSCs due to their widespread sources, easy access and multipotency [3, 8]. More importantly, ASCs isolated from aged or osteoporotic humans and animals maintain their osteogenic differentiation capability, making them more promising for autologous cell-based therapy for osteoporosis [9-11]. Their osteogenic differentiation is regulated at transcriptional, post-transcriptional and epigenetic levels.…”
Section: Introductionmentioning
confidence: 99%